Manufacturing engineering handbook - 4 0 16; Geng, Hwaiyu; 5 (New York : McGraw-Hill, 2004)
LET OUR EXPERT TEAM HELP YOU STAY COMPETITIVE IN THE GLOBAL MARKETPLACE It is every company's goal to build the highest quality goods at the lowest price in the shortest time possible. The Manufacturing Engineering Handbook provides all the information needed to optimize the design of manufacturing processes. This book includes conventional metalworking plus the latest manufacturing and automation technologies, including: * Hot working * Metalforming * Moldmaking * Machine design * Robotics * Machine vision * Surface preparation * Lean manufacturing * Supply chain material control * Productive Maintenance * Much more Written by a team of international experts, the Manufacturing Engineering Handbook details both conventional and emerging manufacturing tools and processes, covering crucial manufacturing issues like new product development, improving manufacturing yield, implementing automated production facilities, and establishing quality and safety programs. Each chapter in this handbook includes the fundamentals of relevant technology and its industrial application; operational considerations for planning, implementing, and controlling manufacturing processes; and a list of relevant books, technical papers, and websites for additional reading. This inclusive, wide-ranging approach makes the Manufacturing Engineering Handbook the most comprehensive single-volume reference ever published in the field Annotation
1. Business Management -- 2. Product Development and Design -- 3. Manufacturing and Automation and Technologies -- 4. Heating Treating, Hot Work, and Metalforming -- 5. Metal Working and Machine Design -- 6. Surface Preparation and Coating -- 7. Robotics, Machine Vision and Assembling -- 8. Manufacturing Management
Includes bibliographical references and index
English
Keywords: 2 -- 0; 6; Production engineering -- 20; 20; Handbooks and manuals